Pengembangan LKPD Berbasis PBL Pada Materi Pecahan untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa dalam Menyelesaikan Soal Cerita - Rosa Dina; Muhamad Firdaus; Rahman Haryadi (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study was motivated by the low level of students' mathematical problem-solving skills in solving word problems on fraction material and the lack of instructional materials that support active learning. The objectives of this study were to develop a Problem-Based Learning (PBL)-based Student Worksheet (LKPD) on fraction material and to determine its validity, practicality, and effectiveness. This study employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The participants included material experts, media experts, a mathematics teacher, and seventh-grade students of SMP Pesantren Assalam. Data were collected through validation sheets, teacher and student response questionnaires, and mathematical problem-solving tests in the form of pretests and posttests. Percentage analysis was used to determine the validity and practicality of the developed LKPD, while its effectiveness was analyzed using the Normalized Gain (N-Gain) method. The results showed that the developed Problem-Based Learning (PBL)-based Student Worksheet (LKPD) met the criteria of highly valid, highly practical, and effective in improving students' mathematical problem-solving skills on fraction material. These findings were supported by expert validation, positive responses from teachers and students, and improved learning outcomes based on the N-Gain analysis. Therefore, the developed LKPD is suitable for use as an instructional material to support mathematics learning on fraction material.